The politics of false consciousness: hermeneutics of the philosophy of suspicion in Marx, Nietzsche, and Freud - Ochoa Ordóñez, Boris Raúl (Arandu UTIC, 2024)
This article addresses and analyzes the essential principles of the philosophy of suspicion, developed by Karl Marx, Friedrich Nietzsche, and Sigmund Freud, and subsequently synthesized by Paul Ricoeur. The purpose of this research is to elucidate, through a hermeneutic reading of the fundamental texts of these thinkers, how society has constructed a false consciousness that obstructs an accurate understanding and interpretation of reality. The literature review is framed within the context of the classical philosophical tradition, allowing for a concise analysis of the main theories related to reality and consciousness. Subsequently, the specific postulates of the philosophy of suspicion of each author are analyzed, and the social elements subject to the critique of suspicion are examined.